Spatial variability of pH in coffee plants under fertigation and traditional system of fertilizing - Rezende, Fátima Conceição (2012)
The objective of this study was to characterize the soil pH in function of chemical fertilizing through irrigation, andmanually, under the canopy. The crop was drip irrigated during the whole year when water soil tension was 21 kPa. The depth of waterwas defined based on the average reading of soil water potential at 0.10 and 0.30m depths. Soil solution extractors were installed atdepths of 0.10, 0.20, 0.30, 0.40 and 0.50 m and distanced from the plant at 0.10, 0.20, 0.30, 0.40 and 0.50 m. The soil pH wasmonitored in the fertilizing period for 2 seasons (2008/2009 and 2009/2010). Evaluation was carried out 24 hours after eachapplication of fertilizer until at least sixty days after the last parceling. Exponential and spherical semi-variogram models wereadjusted applying minimum weighted square and maximum likelihood methodologies, testing the adherence based on spatial dependencedegree and cross validation. The mapping was done based on the best adjusted semi-variogram, using kriging. The results showedthat soil solution pH present spatial dependence in the area sampled. The sources and rates of fertilizer used promoted the alkalinizationof the solution. Soil solution pH tends to be lower in the area with fertigation.